The role of mural painting in the beautification of the cities - Mohammed Abdul Hassan Odeh Al-Anzi (Genius Journals, 2022)
The research presents a case study of the role of mural painting in the beautification of cities. For this reason, the researcher presented in the first chapter the research problem, and the focus was on studying the multiplicity of roles of mural painting in revealing the aesthetics in the spaces of cities and methods of beautifying them in different environments and places and their aesthetic and functional role in the structure of creative work. The aim of the research: to reveal the role of mural painting and its importance in the case of beautifying and decorating cities, while in the second chapter is the theoretical framework. The researcher divided it into two sections, titled the first (the first topic: mural painting between the multiplicity of techniques and heterogeneity in methods), in which the diversity of techniques and mechanisms of their work in mural painting and the impact of environments on the formation of styles and methods of expression within spatial and architectural spaces was revealed. The second topic: diversity of methods and methods of implementation in mural painting), Where the role of mural painting, techniques, and materials in the art and the context of its presence were studied, and then the creative experiences of mural art in the world, civilizations and cultures were followed, while in the third chapter the researcher dealt with the working mechanisms of mural painting in the spaces of cities in Europe and America .. In which the researcher presented a study of the technical and performance variables of mural painting in the beautification of architectural places and spaces. As for the fourth chapter, the researcher reached the results, including that the visual and technical outputs in mural painting represent an aesthetic addition in the place and in the case of beautifying cities and enhancing their role in establishing an effective structural pattern and declaring a cultural identity for the city that affects the aesthetic awareness of the masses, the mural while present in the organization of urban space, is concerned with the type of textures and colors of the wall to employ shapes and elements in a link with the surrounding space
Keywords: Mural painting; city’s identity; plastic art